Learning English Pronunciation through Social Media Tiktok Account - Adityo; Novitasari, Lya (Universitas Nahdatul Ulama Surabaya, 2023)
Abstract - Pronunciation is one of the critical aspects of English that students should learn. In oral communication, the pronunciation should be able to produce sounds that other speakers can understand because speaking English requires this part. This study analyzed how students can learn English Pronunciation through the TikTok application, primarily through Antonio Parlati's videos on his account. Participants are the colleges from five semesters at the English Language Department that have been selected in this research of fourteen participants that were eligible with the researcher's requirement. This study used a quasi-experimental design, considering pre-test, mid-test, and post-test. The test used ten words explained in Antonio Parlati's video on his TikTok. Participants get treatment from the researcher to pronounce the ten words in the pre-test, and before the mid-test and post-test, they should learn the ten words from Antonio's video. The study's findings indicated that learning English Pronunciation from Antonio Parlati's video on his TikTok significantly affects the participants' pronunciation. From the explanation from Antonio's video, participants can improve their English pronunciation with the fun and enjoyable method following this study.